The backpack of a Carinthian Slovene – transmission of transgenerational trauma in Slovenes in Carinthia/Koroška - Wirth, Luisa (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2022)
During the time of National Socialism, the Slovenes in Carinthia/Koroška were persecuted. The present study examines the transmission of transgenerational trauma in Carinthian Slovenes. Qualitative problem-centred interviews were conducted with second generation Carinthian Slovenes and analysed with psychoanalytic text interpretation. Even though there were no indications of trauma disorders in the present sample, there was clear evidence of mental burden linked to many of the respondents’ family histories. The familial past was often experienced as a burden. The experiences of the first generation seemed to have a significant impact on the second generation. The study holds important implications for the psychotherapeutic treatment of the offspring of Holocaust survivors and highlights the societal responsibility to acknowledge the trauma of oppression and persecution.
Keywords: fotoelicitacija; koroški Slovenci; kvalitativna metodologija; medgeneracijski prenos travme; psihoanalitična interpretacija besedila; travma